Lessons of history : Learning from catastrophe and crisis in twentieth-century Europe (Berghahn Books, 2025)
Historical lessons are useful or even necessary for our guidance and orientation in time. These lessons, however, have often been overlooked in historical reflections on watershed moments, such as genocides, treaties, and global movements. Focusing on how cataclysmic events, primarily within Central and Eastern Europe, have been transmitted across borders and generations, this volume interrogates how the theory of historical lessons has evolved, ultimately providing a useful framework for understanding contemporary conflicts and issues. Spanning topics from the mediation of history within film to the influence of historical oppression on student activism, this volume re-evaluates historiography's potential for analyzing the past and engaging with the present.
Publisher Copyright: © 2025 Klas-Göran Karlsson and Maria Karlsson. All rights reserved.